Flow and Heat Transfer Analysis of Williamson Viscous Fluid on the Stagnation Point Past a Stretching Surface with Viscous Dissipation and Slip Conditions - Hasmawani, Hashim; Muhammad Khairul Anuar, Mohamed; Abid, Hussanan; Nazila, Ishak; Norhafizah, Md Sarif; Mohd Zuki, Salleh (Universiti Malaysia Pahang, 2016)
The stagnation flow and heat transfer of a Williamson viscous fluid towards a stretching surface with slip conditions and viscous dissipation is studied. With the help of similarity transformation, the governing equations are converted to nonlinear ordinary differential equations and then solved numerically by Runge-Kutta-Fehlberg (RKF) technique. Numerical results for the local Nusselt number and skin friction coefficient as well as the temperature and velocity field are elucidated through tables and graphs. The influence of Prandtl number, stretching parameter, non-Newtonion Williamson fluid parameter, Eckert number, thermal and velocity slip parameter on the flow and heat transfer characteristics are analyzed and discussed.